In Vitro Effect of MRSAc in Bacteriocins Produced from MRSA on Propionibacterium Acnes Comparing with Antibiotics - Mais E. Ahmed (Journal of Global Pharma Technology, 2018)
Propionibacterium acnes most isolation higher in female than male (14% and 4%) respectively all strain resistance antibiotic and using purification Bacteriocins from MRSA isolation from wound to control acne vulgaris. In this study, Futurity one skin swabs were obtained from patients suffering from acne vulgaris from consultation unit in Baghdad teaching Hospital, from both sexes. Ten isolates (18%) of anaerobic gram positive Probionibacterium acnes were identified and diagnosis by culture, Api 20A system, Resistance to antibiotics and Vitek 2 ANC System. The local isolation Methicillin-resistant Staphylococcus aureus MRSA strain from wound specimen diagnosis by cultures, Biochemical test and Vitek 2 ANC System. It was found that P. acne isolates were higher in female than male (14% and 4%) respectively, and more prevalence in age (16-21) years patients and lower in older age. The effect of some antibiotics on Probionibacterium acnes was investigated, and the results showed that all isolates were resistance to antibiotics (Azithromycin, Erythromycin, Metronidazole and Clindamycin) and have been sensitive to (Levofloxacin). There is a need potently replacements to antibiotics to axing the impedance to treat acne infections. Purified bacteriocin (MRSAcin) produce from using against resistance P. acnes their wide inhibition zone by the well diffusion assay (WDA) method and Paper disc method reached (15 and 11) mm respectively at concentration 62.5 µg/ml compared with sensitive antibiotic disc of Levofloxacin that diameter reached 9mm. The current in vitro study proved that P. acne was resistant to most antibiotics except levofloxacin. Bacteriocins (MRSAcin) had a good antibacterial activity and its effects exceed the effects of levofloxacin antibiotic.Keywords: Bacteriocin, MRSA, P. acnes